Severe jaundice post embryo transfer: a case report - Mustafa, Kamarul Bahyah; H. , Abdul Hamid; A. K., Abdul Karim; N.A. , Mohd Nor; M.H., Omar; Z.R., Mohd Razi (CIC Edizioni Internazionali, Roma, 2014)
Jaundice related to embryo transfer or in early pregnancy after in vitro fertilization with or without ICSI is extremely rare. We report a case of severe jaundice in an IVF treated patient who is not successfully pregnant, with a clinical picture similar to intrahepatic cholestasis.